2016
DOI: 10.1152/japplphysiol.00928.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isolation and confinement on humans-implications for manned space explorations

Abstract: Human psychology and physiology are significantly altered by isolation and confinement. In light of planned exploration class interplanetary missions, the related adverse effects on the human body need to be explored and defined as they have a large impact on a mission's success. Terrestrial space analogs offer an excellent controlled environment to study some of these stressors during a space mission in isolation without the complex environment of the International Space Station. Participants subjected to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 57 publications
1
85
0
3
Order By: Relevance
“…It has been established that crew members participating in such terrestrial missions also shed latent herpesviruses 41. Similarly, better controlled laboratory simulations of spaceflight confinement, such as a recent Russian 500-day Mars simulation, have also been found to re-create immune dysregulation, which shares some aspects of flight-associated dysregulation 42. We suggest monitoring strategies and countermeasures developed to assess and prevent incidence in astronauts may facilitate the reduction of illness on Earth.…”
Section: Discussionmentioning
confidence: 85%
“…It has been established that crew members participating in such terrestrial missions also shed latent herpesviruses 41. Similarly, better controlled laboratory simulations of spaceflight confinement, such as a recent Russian 500-day Mars simulation, have also been found to re-create immune dysregulation, which shares some aspects of flight-associated dysregulation 42. We suggest monitoring strategies and countermeasures developed to assess and prevent incidence in astronauts may facilitate the reduction of illness on Earth.…”
Section: Discussionmentioning
confidence: 85%
“…It has been demonstrated that this inhospitable environment represents also a suitable and standardized Earthbound analogue to mimic some factors like monotonous surroundings, repetitive daily routine and confinement, and its possible resulting psycho-social stress that humans are subjected to during long-term spaceflights [1][2][3]. General findings in respective studies describe hormonal changes due to an altered biological rhythm [4] which directly affects sleep pattern and quality [5][6][7] as well as psycho-social behavior [8].…”
Section: Introductionmentioning
confidence: 99%
“…A review by Pagel and Chouker outlined that isolation can impact cognitive performances, stress levels and psychological strain (37). Our questionnaire was designed to assess psychological strain during the isolation period at the Concordia station.…”
Section: Discussionmentioning
confidence: 99%